+0  
 
0
170
1
avatar

Write the following expression as a polynomial: (2x^2+3x+7)(x+1)-(x+1)(x^2+4x-63)+(3x-14)(x+1)(x+5).

 Jun 30, 2019
 #1
avatar+106981 
+1

(2x^2+3x+7)(x+1)-(x+1)(x^2+4x-63)+(3x-14)(x+1)(x+5).

 

\((2x^2+3x+7)(x+1)-(x+1)(x^2+4x-63)+(3x-14)(x+1)(x+5)\\ =(x+1)[(2x^2+3x+7)-(x^2+4x-63)+(3x-14)(x+5)]\\ =(x+1)[(2x^2+3x+7)-(x^2+4x-63)+(3x^2+x-70)]\\ =(x+1)[(2x^2+3x+7-x^2-4x+63+3x^2+x-70]\\ =(x+1)[4x^2+140]\\ =4(x+1)[x^2+35]\\ =4[x^3+35x+x^2+35]\\ =4x^3+140x+4x^2+140\\\)

.
 Jun 30, 2019

40 Online Users

avatar
avatar